Comorbidity in acute heart failure complicating myocardial infarction - M. V. Zykov; V. V. Kashtalap; I. S. Bykova; V. A. Poltaranina; O. L. Barbarash; S. A. Raff; E. D. Kosmacheva; A. D. Erlikh (Российский кардиологический журнал, 2020)
Aim. To study the relationship between comorbidity and acute heart failure (AHF) complicating myocardial infarction (MI).Material and methods. The analysis included 993 patients with MI from the registry of acute coronary syndrome RECORD-3. Killip class II-IV was recorded in every fifth patient (n=205). Hospital mortality was 6,3%. The mean age was 64,3 (63,5-65,0) years (men — 66,1%). All patients were divided into three groups depending on the number of comorbidities (type 2 diabetes, chronic kidney disease, atrial fibrillation, anemia, stroke, hypertension, obesity, peripheral atherosclerosis, thrombocytopenia). The first group included patients with no more than one disease (n=251), the second one — with 2 or 3 diseases (n=480), and the third one — with 4 or more diseases (n=262).Results. AHF detection rate increased in groups with increasing comorbidity: 12,3%, 17,9% and 33,6%, respectively (p<0,0001). Regardless of the initial therapy, in patients of the first group without AHF the hospital mortality rate did not exceed 1%. In patients of the third group with Killip class II-IV AHF the hospital mortality was the highest and also did not depend on the choice of treatment strategy (24,6% with conservative management, 31,6% with percutaneous coronary intervention (PCI)). PCI made it possible to reliably (p<0,05) reduce the risk of hospital mortality in patients of the second and third groups without AHF relative risk 4,3 (1,0-19,9) and 4,2 (1,1-18,3), respectively. Analysis of a 1-year follow-up revealed that AHF is a death predictor after hospital discharge independent of the comorbidity severity: 11,1%, 13,3%, and 14,3%, respectively. In patients without AHF a 1-year mortality increased from the first to the third group: 1,1%, 5,8% and 7,0%, respectively (p=0,043).Conclusion. Сomorbidity is an independent predictor of heart failure in MI, and their combination is associated with the most unfavorable in-hospital prognosis, regardless of the treatment strategy. The greatest advantage of PCI for reducing the hospital mortality rate was obtained in patients with comorbidity and without manifestations of AHF.